2019
DOI: 10.21608/mjcu.2019.78253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Two Different Anesthetic Techniques on Immune Response and Postoperative Pain for Abdominal Hysterectomy

Abstract: Background: Spinal anesthesia is a famous technique used for lower abdominal surgery, however when it is contraindicated, general anesthesia can be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…We suggested that the use of SA for cesarean section in preeclampsia patients may slow the increase in cytokines after surgery. Contradictory to our results, Mohammed Ashery et al (17) showed that at 30 minutes after anesthesia induction and at four hours postoperatively, the levels of IL-6 and TNF were significantly higher in the SA group compared to the GA group in benign abdominal hysterectomy. The level of anti-inflammatory IL-10 also significantly increased in the GA group at four hours after surgery as compared to the SA group.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We suggested that the use of SA for cesarean section in preeclampsia patients may slow the increase in cytokines after surgery. Contradictory to our results, Mohammed Ashery et al (17) showed that at 30 minutes after anesthesia induction and at four hours postoperatively, the levels of IL-6 and TNF were significantly higher in the SA group compared to the GA group in benign abdominal hysterectomy. The level of anti-inflammatory IL-10 also significantly increased in the GA group at four hours after surgery as compared to the SA group.…”
Section: Discussionsupporting
confidence: 76%
“…We did not find any significant difference in the concentration of IL-10; also, no significant difference was found in the ratio of IL-6 changes to IL-10 changes or TNF-α changes to IL-10 changes between the two groups. The reason may be that the IL-10 level usually rises hours after the operation, while we measured postoperative cytokines only 30 minutes after surgery (12,17). Interestingly, Malamitsi-Puchner et al (15) found that b There was a significant difference between the groups.…”
Section: Discussionmentioning
confidence: 90%